Treatment of limited stage follicular lymphoma with Rituximab immunotherapy and involved field radiotherapy in a prospective multicenter Phase II trial-MIR trial - Witzens-Harig, Mathias; Hensel, Manfred; Unterhalt, Michael; Herfarth, Klaus (BMC cancer, 2011)
The optimal treatment of early stage follicular Lymphoma is a matter of debate. Radiation therapy has frequently been applied with a curative approach beside watchful waiting. Involved field, extended field and total nodal radiation techniques are used in various protocols, but the optimal radiation field still has to be defined. Follicular lymphoma is characterized by stable expression of the CD20 antigen on the tumour cells surface. The anti CD20 antibody Rituximab (Mabthera®) has shown to be effective in systemic therapy of FL in primary treatment, relapse and maintenance therapy.
Gesehen am 21.11.2022